2021
DOI: 10.3390/ijerph18063035
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness among Homeless Individuals during the First Wave of the COVID-19 Pandemic

Abstract: The feeling of loneliness is a major public health concern associated with multiple somatic and psychiatric illnesses. Studies have shown increasing incidence of loneliness in the general population during the first wave of the COVID-19 pandemic. Homeless individuals are a particularly vulnerable group; however, little is known about loneliness among homeless individuals. We therefore aimed to examine the prevalence of loneliness among homeless individuals during the pandemic. Furthermore, we estimated the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…Fear or perceived threat of COVID-19 among PEH was discussed by ten studies [ 12 , 13 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ]. Fear varied across studies; in Los Angeles, 65% of tenants of permanent supportive housing surveyed by Henwood et al [ 85 ] in March 2020 regarded COVID-19 as a serious risk to their health, while 33% of those surveyed in Los Angeles by Kuhn et al [ 87 ] from December 2020 to February 2021 perceived it as a high threat.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fear or perceived threat of COVID-19 among PEH was discussed by ten studies [ 12 , 13 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ]. Fear varied across studies; in Los Angeles, 65% of tenants of permanent supportive housing surveyed by Henwood et al [ 85 ] in March 2020 regarded COVID-19 as a serious risk to their health, while 33% of those surveyed in Los Angeles by Kuhn et al [ 87 ] from December 2020 to February 2021 perceived it as a high threat.…”
Section: Resultsmentioning
confidence: 99%
“…PEH’s perceived threat of COVID-19 impacted some aspects of their health and behaviour. In one study, increased loneliness was associated with a high self-perceived risk of contracting COVID-19 [ 84 ]. Kuhn et al [ 87 ] reported PEH in their study who perceived the virus as a high threat were significantly less likely to be vaccine hesitant.…”
Section: Resultsmentioning
confidence: 99%
“…This is considerably higher than figures from COVID-19 research on the US adult population, which saw loneliness increase from 11% in 2018 to 13.8% in April 2020 ( McGinty et al, 2020 ). German data collected during Spring 2020 also found roughly 50% of homeless persons were experiencing loneliness, compared to 11% of the national population ( Bertram et al, 2021 ). Moreover, depressed participants within our study were significantly more likely to worry about remaining isolated.…”
Section: Discussionmentioning
confidence: 99%
“…27 Responses to the three items were summed, creating a variable ranging from 0 to 6. In line with previous use of this scale, [28][29][30] we considered loneliness as a continuous outcome.…”
Section: Lonelinessmentioning
confidence: 99%